2015
DOI: 10.1016/j.actbio.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Creating capillary networks within human engineered tissues: Impact of adipocytes and their secretory products

Abstract: The development of tissue-engineered substitutes of substantial volume is closely associated with the need to ensure rapid vascularization upon grafting. Strategies promoting angiogenesis include the in vitro formation of capillary-like networks within engineered substitutes. We generated both connective and adipose tissues based on a cell sheet technology using human adipose-derived stromal cells. This study evaluates the morphology and extent of the capillary networks that developed upon seeding of human mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Fortunately, subcutaneous fat tissue contains a large amount of microvascular EC (MVEC), and in vitro culturing could be avoided [42,43]. Furthermore, skin MVEC have already been isolated and used for tissue engineering [44,45] and would also be an interesting alternative. In a clinical setting, ASC-TEVS could be endothelialized with fat-derived MVEC and DF-TEVS with skin-derived MVEC therefore no additional biopsies would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, subcutaneous fat tissue contains a large amount of microvascular EC (MVEC), and in vitro culturing could be avoided [42,43]. Furthermore, skin MVEC have already been isolated and used for tissue engineering [44,45] and would also be an interesting alternative. In a clinical setting, ASC-TEVS could be endothelialized with fat-derived MVEC and DF-TEVS with skin-derived MVEC therefore no additional biopsies would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 3D co-culture with endothelial cells on porous silk protein matrices could maintain the structure and function of ASC-differentiated adipocytes for at least 6 months (Bellas et al, 2013). In this type of co-culture, there is a mutually enhanced effect between the adipocytes and endothelial cells, which mimics in vivo cell-cell interactions and supports improved adipocyte function, endothelial cell proliferation and capillary network formation (Aubin et al, 2015; Yao et al, 2013a). Moreover, an in vivo study demonstrated the long-term stability of volume and weight of the injected HUVEC-adipocytes within collagen/alginate microspheres, indicating that vascularization facilitates the formation, maturity, and maintenance of the adipose tissue (Yao et al, 2013b).…”
Section: 3d Microenvironments To Control Adipogenesis Of Stem Cellsmentioning
confidence: 94%
“…ASCs extracted from liposuctions can be expanded in culture and used as building blocks for tissue engineering. Both connective and adipose tissues were engineered in vitro using ASCs [31][32][33]. Both allogeneic and xenogeneic ASCs can be transplanted in patients regardless of their immunocompatibility and without the need of immunosuppression therapy, making them an unlimited source for regenerative medicine applications [34].…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%